Determinants of crime rates: Crime Deterrence and Growth in post-liberalized India - Dutta, Mousumi
Becker’s analysis of crime and punishment has initiated a series of theoretical and empirical works investigating the determinants of crime. However, there is a dearth of literature in the context of developing countries. This paper is an attempt to address this deficiency. The paper investigates the relative impact of deterrence variables (load on police force, arrest rates, charge sheet rates, conviction rates and quick disposal of cases) and socio-economic variables (economic growth, poverty,, urbanization and education) on crime rates in India. State-level data is collected on the above variables for the period 1999 to 2005.Zellner’s SURE model is used to estimate the model. Subsequently, this is extended by introducing endogeneity. The results show that both deterrence and socioeconomic factors are important in explaining crime rates. However, some of their effects are different from that observed in studies for developed countries.Crime, Deterrence, Growth, India, SURE Model